Early Right Ventricular Systolic Dysfunction and Pulmonary Hypertension Are Associated With Worse Outcomes in Pediatric Acute Respiratory Distress Syndrome. Issue 11 (November 2018) - Himebauch, Adam S.; Yehya, Nadir; Wang, Yan; Conlon, Thomas; Kilbaugh, Todd J.; McGowan, Francis X.; Mercer-Rosa, Laura
Abstract : Objectives: The prevalence and importance of early right ventricular dysfunction and pulmonary hypertension in pediatric acute respiratory distress syndrome are unknown. We aimed to describe the prevalence of right ventricular dysfunction and pulmonary hypertension within 24 hours of pediatric acute respiratory distress syndrome diagnosis and their associations with outcomes. Design: Retrospective, single-center cohort study. Setting: Tertiary care, university-affiliated PICU. Patients: Children who had echocardiograms performed within 24 hours of pediatric acute respiratory distress syndrome diagnosis. Interventions: None. Measurements and Main Results: Between July 1, 2012, and June 30, 2016, 103 children met inclusion criteria. Echocardiograms were analyzed using established indices of right ventricular and left ventricular systolic function and for evidence of pulmonary hypertension. Echocardiographic abnormalities were common: 26% had low right ventricular fractional area change, 65% had low tricuspid annular plane systolic excursion, 30% had low left ventricular fractional shortening, and 21% had evidence of pulmonary hypertension. Abnormal right ventricular global longitudinal strain and abnormal right ventricular free wall strain were present in 35% and 40% of patients, respectively. No echocardiographic variables differed between or across pediatric acute respiratory distress syndrome severity. In multivariable analyses, right ventricular global longitudinal strain was independently associated with PICU mortality (odds ratio, 3.57 [1.33–9.60]; p = 0.01), whereas right ventricular global longitudinal strain, right ventricular free wall strain, and the presence of pulmonary hypertension were independently associated with lower probability of extubation (subdistribution hazard ratio, 0.46 [0.26–0.83], p = 0.01; subdistribution hazard ratio, 0.58 [0.35–0.98], p = 0.04; and subdistribution hazard ratio, 0.49 [0.26–0.92], p = 0.03, respectively). Conclusions: Early ventricular dysfunction and pulmonary hypertension were detectable, prevalent, and independent of lung injury severity in children with pediatric acute respiratory distress syndrome. Right ventricular dysfunction was associated with PICU mortality, whereas right ventricular dysfunction and pulmonary hypertension were associated with lower probability of extubation. Abstract : Supplemental Digital Content is available in the text.